Development and validity evidence on the scale of perceived social support for university students (EPSSEU) during the period of social restrictions - Thaís Calcagno Vidon Bruno; Isis Danyelle Dias Custódio; Luiz Antônio Alves de Menezes-Junior; Adriana Lúcia Meireles; Ana Cláudia Morito Neves; Sabrina Martins Barroso; Júlia Cristina Cardoso Carraro (BMC, 2024)
Abstract Aim This study aims to validate a Perceived Social Support Scale for University Students (EPSSEU) during periods of social restrictions, by focusing on family and university support. Subject and methods This cross-sectional study was conducted with undergraduate students from a public higher education institution. The college students who participated in the study-1353 at baseline and 378 after 6 months-answered a virtual questionnaire containing questions on: sociodemographic and lifestyle data, items proposed for the EPSSEU, Satisfaction with Social Support Scale (ESSS), and Depression, Anxiety and Stress Scale (DASS-21). Exploratory factor analysis, Cronbach's alpha reliability analysis, as well as discriminant, convergent, and known-group validations were performed. Results The results showed two factors support from: i) the university and ii) friends and family- which explained 61.82% of the variance in the data. The EPSSEU showed good reliability (Cronbach's alpha = 0.796) as well as validity, with higher scores among individuals without depression, anxiety, or stress. Conclusion The EPSSEU shows adequate psychometric qualities and may be a useful instrument for assessing university students' social support in pandemics, social distancing, and remote teaching contexts.